Case report: A case of widespread soft tissue infection and multiple abscesses secondary to hidradenitis suppurativa inducing septic shock caused by Lawsonella clevelandensis in China - Zhi Lijia; Qi Jia Chao; Li Li; Deng Shikun; Gao Peiyang (Frontiers in Medicine, 2024)
Lawsonella clevelandensis is rare to associated with human infection, which may cause abscesses in abdominal cavity, liver, breast, and spine. Lawsonella clevelandensis is very difficult to be cultivated in regular manner; detection of 16S rRNA sequence is the main evidence for L. clevelandensis infection. The clinical manifestations of L. clevelandensis infection resemble other agents of Nocardia, Tuberculosis and non-tuberculous Mycobacterium (NTM) due to their morphologic similarities. Hidradenitis suppurativa (HS) is a chronic inflammatory disorder, which affects the intertriginous skin and is associated with numerous systemic comorbidities. HS eventually leads to severe pain, multiple abscesses, pus discharge, and irreversible tissue destruction. Lawsonella clevelandensis has not been reported to cause HS and systemic comorbidities. We presented the case of a 33-year-old male with widespread soft tissue infection and multiple abscesses secondary to HS (Hurley stage III) inducing septic shock caused by L. clevelandensis in China. He was diagnosed as HS and treated with intravenous antibiotic empirically. He developed multiple abscesses including lung and scrota. Bacterial and fungal cultures on blood and secretions from multiple skin lesions were all negative. Due to the misdiagnosis and progression of disease, the patient was transferred to intensive care unit, and he underwent drainage of the chest and right hemothorax removal under thoracoscopic. During the hospitalization, the patient developed septic shock and received mechanical ventilation. Computerized tomography (CT) scans revealed mediastinal emphysema, multiple subcutaneous emphysema, and severe pneumonia. Gene analysis of samples of incision and drainage of pus at the skin showed the rare infection of L. clevelandensis. Finally, the patients with recurrent soft tissue infections and multiple abscesses with negative microbiological culture results recovered after effective abscess drainage and antibiotic therapy. We suggested that NGS is a crucial supplementary diagnostic tool in individuals with recurrent skin infections and multiple abscesses, especially when conventional diagnostic methods are inconclusive.